Da linguagem à memória: uma análise dos gêneros discursivos desenvolvidos na história da TV Cultura - Silva, Thiago Rodrigues da (2018)
Television has acquired the power to influence the development of subjects with a high level of reach in the social categories of individuals providing simultaneous communication to different places. With these characteristics, TV Cultura reaches worldwide appreciation for the enrichment that it provides to society under a narrative that is considered synonymous with commitment to the creation of a program that values to serve the varied population and that surpasses the objectives established by the market. The research proposed here aimed to analyze the way in which TV Cultura seeks to construct its statements, recognized as discursive genres. The television channel that is born with the mission to constitute opinion-forming individuals, diffusers of knowledge and culture can reproduce their intentions through the choice of their speech mode, bringing the hypothesis that the reasons that make the broadcaster able to have its productions remembered by the population are the genres that it presents. For the recognition of these marks of the programming constructed by the channel, the paths developed by Mikhail Bakhtin are used to establish the relation of the language with its surroundings and proposing as a method the comparison that allows to recognize other voices and texts capable of materializing the link between the television and society. Discursive genres become sources of knowledge through the language that reaches the viewer and it is from this language, which is considered important for the viewers, is what makes memory present, consolidated in the desire to keep the programming alive and in the molds that made it recognized as quality. The search for a political, social and cultural analysis of the situation and history of the channel is fundamental so that one can understand how it is possible to establish a quality public television network and that it can actually fulfill its paper.